BEYOND THE EFFICIENT MARKET HYPOTHESIS: A CONCEPTUAL INQUIRY INTO CALENDAR ANOMALIES - Shehryar, Muhammad; Mardoni, Yosi; Anser, Muhammad (JRAK, 2025)
Calendar anomalies, including the day-of-the-week effect, week-of-the-month effect, and January effect, persistently contest the efficient market hypothesis (EMH), which asserts that asset prices completely incorporate available information. This study reviews previous research to explore why these predictable patterns persist despite technological progress and market transparency. By combining perspectives from EMH, behavioral finance, and the adaptive market hypothesis (AMH), the study explains the temporal variability of these anomalies across different market contexts. Results demonstrate that investor sentiment, cognitive biases, and socio-cultural influences largely contribute to their persistence. The discourse encompasses practical implications for investment strategy, portfolio management, and regulatory surveillance, particularly highlighting Shariah-compliant and emerging markets where anomalies may display unique attributes. Investors, mutual funds, and brokers can gain benefit through generating higher returns.